Divide and Choose as Dual Participatory Justice: A Comparative Framework for UAE Civil Disputes - Chami, Yassine; Dran , Driss ed (Legality : Jurnal Ilmiah Hukum, 2026)
This study introduces a novel conceptual model, "Dual Participatory Procedural Justice," as a theoretical legal framework for implementing the "Divide and Choose" principle in bilateral divisible disputes in private law, addressing contemporary challenges in civil and commercial dispute resolution. This system diverges from the mathematical idealism of Western theory and the fragmented applications of traditional Islamic jurisprudence by integrating the procedural precision of Game Theory with Islamic legal maxims, especially the principles of preventing harm and alleviating hardship. Employing a critical comparative methodology grounded in Natural Law jurisprudence, the study challenges the prevailing notion of symmetry in Western models and contextualises the mechanism within the historical operational frameworks of Islamic courts. The resulting framework establishes enforceable safeguards, including mandates for functional symmetry and expert intervention. The study primarily focuses on situating the proposal within the framework of UAE Civil Procedure Law and constitutional Sharia principles, while offering a comparative analysis of its applicability in Southeast Asian jurisdictions, particularly highlighting parallels with the Indonesian Musyawarah and Malaysian Sulh systems. The model is only for disputes that can be split into two and does not cover issues of child custody or public policy (ordre public). The results show that this participatory approach significantly reduces court backlogs and makes people in Arab and Southeast Asian countries happier with the law.